Effect of Leaves Infuse (Foeniculum vulgare Mill.) Intake on Reproductive Organs Morphometry of Female Rats (Rattus Sp.) After Parturition - Rifqiyati, Najda; Sholihah, Jumailatus; Soimah, Laelatul (Proceeding International Conference on Science and Engineering, 2017)
Fennel (Foeniculum vulgare Mill.) traditionally used by people as antifertility agent for female. Fennel leaves (Foeniculum vulgare Mill.) contain phytoestrogen that has role as antiestrogen or synthesized become antiestrogen. Coumarin is the kind phytoestrogen that can be antiestrogen to female reproductive organs such as ovary and utery. The aim of this research is to find out the influence of fennel leaves infuse (Foeniculum vulgare Mill.) on morphometric of ovary and utery in female rats (Rattus sp.) administered after parturition, to find out the effective dose affecting the morphometric of ovary and utery and to find out the total coumarin consisted in fennel leaves (Foeniculum vulgare Mill.). This research was carried out by using CRD (Completely Randomized Design) consisted of 2 groups, those are control group (aquades) and treatment groups (doses of fennel leaves infuse 20 g/300 ml, 40 g/300 ml and 60 g/300 ml). The treatment was administered in the morning and afternoon for 15 days. After 15 days of treatment, the rats were sacrificed and dissected to measure the morphometry of reproductive organs (ovary and utery). The data obtained was analyzed by Analysis of Varian (ANOVA) and continued by LSD (Least Significance Different) test with significance of 5%. The measurement of coumarin level was performed by TLC (Thin Layer Chromatography) densitometry method. The result of this research showed that the administration of infused fennel leaves (Foeniculum vulgare Mill.) at dose of 20 g/300 ml, 40 g/300 ml and 60 g/300 ml significantly decreased ovarian weigh in female rats (Rattus sp.) after parturition (p<0,05), but not decreased the length, width, thick of ovary, length and diameter of utery (p>0,05). No difference was observed between doses 20 g/300 ml, 40 g/300 ml and 60 g/300 ml, and it showed that the dose 20 g/300 ml of fennel leaves infuse was able to be used to decrease the weigth of ovary. Coumarin level observed in leaves is 0,09%, and it is higher than the coumarin content in fruit/seed.